The link between small reservoir infrastructure and farmer-led irrigation: case study of Ogun Watershed in southwestern Nigeria - Oke, Adebayo; Cofie, Olufunke O.; Merrey, Douglas J. (International Water Management Institute, 2023)
Small water infrastructure in Nigeria needs to be utilized more efficiently. There are over 900 small reservoirs across the country. Many of these have yet to be put to productive use within the Ogun watershed in the Ogun Osun River Basin. This study investigates the challenges and opportunities for improving the use of small reservoirs for farmer-led irrigation in a sustainable way. The 20 small reservoirs investigated showed varying degrees of degradation of the hydraulic structures, poor embankment maintenance evidenced by the observed erosion, overgrown shrubs, spillway cracks and failures, and siltation of the reservoir. Poor water management and irrigation practices due to weak technical capacity are also observed. There needs to be a precise governance arrangement or policy supporting water use in such a situation. The economic interests and considerations of the farmers determine the irrigation activities around the reservoirs. Regulations and management of the reservoirs were based on what was considered appropriate by the farmers. With the increasing interest in the use of small reservoirs as water sources for farmer-led irrigation in Nigeria, increased capacity building and training, access to agricultural inputs, finance, and the transformation of commodity associations to water users’ associations would contribute to improving the productivity of small reservoirs.